Does Female Reservation Affect Long-Term Political Outcomes? Evidence from Rural India - Deininger, Klaus (2012)
Although many studies have explored the impacts of political quotas for females, often with ambiguous results, the underlying mechanisms and long-term effects have received little attention. This paper uses nation-wide data from India spanning a 15-year period to explore how reservations affect leader qualifications, service delivery, political participation, local accountability, and individuals willingness to contribute to public goods. Although leader quality declines and impacts on service quality are often negative, gender quotas are shown to increase the level and quality of women's political participation, the ability to hold leaders to account, and the willingness to contribute to public goods. Key effects persist beyond the reserved period and impacts on females often materialize only with a lag.